How to develop student creativity through teaching materials of reaction rate STEM-based? - S D W Tahir; S Anwar (Pascasarjana Universitas Pendidikan Indonesia, 2018)
The purpose of this research is to produce teaching materials (reaction rate) based on STEM to develop student creativity. The research method using is Development Research, the method of development of teaching materials used is Four Steps Teaching Material Development (4S-TMD). This article is the first part of the development of teaching materials that includes the steps of selection and structuring. The selection steps consists of the development of indicators, the selection of concept labels, the selection of concept definitions derived from international textbooks, and the development of aspects of STEM. The steps of structuring is organizing concepts and materials into concept maps, macro structures, and multiple representations. The results of the first two steps of this study are the design of STEM-based teaching materials. The evaluation of the draft of teaching materials is done by an expert lecturer in the field of chemical education to assess the feasibility of teaching materials. The result of the research indicates that the teaching material developed has been in accordance with the curriculum requirement, has guaranteed the scientific truth, the value and the STEM aspect in accordance with the subject, and the concept map, macro structure, multiple representations developed are valid.